Existency of Women Leadership at Village Level and Its Orientation against Gender Justice (Case Studies in Banda Aceh and Aceh Besar) - Munawiah Munawiah; Ernita Dewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Women's leadership at the village level is a new thing for the people of Aceh today, because previously it was very rare. Becoming a leader at the village level known as a keuchik is not easy, they face many challenges and obstacles. Moreover, in initiating and running pro-women programs. However, the community has been familiar with programs that are general in nature, not looking at gender sensitive. Village development, for example, is more focused on physical construction in the form of buildings, open non-physical development such as increasing the number of women who get education, support for women's economic empowerment and also concern for increasing health awareness for women.